Rastreamento de lesões orais e avaliação clínico-patológica: um estudo retrospectivo de 10 anos em uma região do Nordeste brasileiro - Ximenes, Iury da Silva (2022)
The oral cavity is affected by several diseases and, in order to establish a correct diagnosis, it is important for professionals to know about these lesions. Clinicopathological surveys represent an important tool for tracking oral lesions with the function of facilitating and guiding the diagnostic process. The objective of the study was to identify the main oral lesions diagnosed by the oral cancer screening of the Ceara State Health Department (SESA), seeking to recognize the profile of these lesions in the geographic regions. This is a retrospective observational study, where the histopathological reports of SESA were collected, between the years 2009 to 2019. Sociodemographic data such as sex, race, age and health region were collected, as well as clinical data of the lesion, such as anatomical location, diagnostic hypothesis, histopathological diagnosis, biopsy date and report release date. Data were tabulated in Microsoft Excel and exported to SPSS v20.0, in which analyzes were performed with a confidence level of 95%. Absolute frequency and percentage of each of the variables were performed using the chi-square test and multinomial logistic regression. 4,501 histopathological reports were collected, more female patients (61.3%), brown (53.4%), between the fourth and sixth decade of life (34%) and from the Ceara sertão region (35,5%). The gingiva/sulcus region was the most affected anatomic site (23%) and, among all lesions, benign ones were the most prevalent (86.6%). Among the most recurrent benign lesions are fibroepithelial hyperplasia/inflammatory fibrous hyperplasia, mucocele and traumatic fibroma; Squamous Cell Carcinoma (SCC) was the most frequent malignant lesion. Dentists had a greater agreement between the diagnostic hypothesis (HD) and the histopathological diagnosis (DH) and, as of 2015, there was a greater agreement compared to the other years (p=0.001). When the lesions affected the belly of the tongue, when they had more than one location or when the professional did not mention the anatomical site, they were more likely to make a mistake in the diagnosis compared to the others (p<0.001). Between the years 2009 and 2011, dentists made more mistakes in diagnosis compared to the other years (p<0.001). A faster release of reports occurred from the second to the fourth quarter of the years (p<0.001) and, in the years 2009 to 2015, there was a longer delay in releasing the reports (p<0.001). Regarding gender, female patients took longer to receive the report compared to males (p=0.023). We conclude that there is a higher frequency of benign lesions throughout the state, mainly reactional and, among the malignant ones, SCC prevailed among all others. In addition, dentists had a greater agreement between HD and HD, especially over the years.